THE DEVELOPMENT OF THE ELECTRIC POWER INDUSTRY AFTER THE OCTOBER REVOLUTION OF 1917: ORIGINS, PROSPECTS AND PROBLEMS - A. A. Gibadullin (Статистика и экономика, 2018)
Purpose of the study. During the period of the fall of technical and technological stability of the Russian electric power industry, the issues related to the study of the historical experience of the origin, construction and development of such large industrial complexes are actualized. The present study aims to analyze the history of the development of the Russian electric power industry after the October Revolution of 1917, to reveal the influence of the revolution on the electric power industry, to investigate the postwar period of the formation of the Unified Energy System and to assess the current state of the electric power industry in the absence of large-scale projects and programs for updating and modernizing production facilities, propose mechanisms to improve technical and technological stability of electricity of the Russian Federation.Materials and methods. In 1920, after the October Revolution of 1917, the first plan related to the development of economic activities of the national economy was adopted, which was called the State Plan for the Electrification of Russia. This document contained the main mechanisms and requirements for the formation and establishment of a new branch for the economy. Based on the use of data from the Government of the Russian Federation, Federal State Statistics Service of the Russian Federation, the Ministry of Energy of the Russian Federation, Joint-stock company “United Energy System of Russia”, as well as electric power companies, the post-revolutionary period of the electric power industry development, the current state and the existing potential of the Russian electric power industry are analyzed. Using the economic-statistical, comparative and logical methods, the main results of the study were presented.Results. Analyzed indices of the electric power industry in the period 1920–1935 indicate a breakthrough in the development of the Russian energy sector, this period was marked by the implementation of the plans ahead of schedule. In the post-war period, from 1950–1985, there was an increase in the construction of production capacities, The development of the electric power industry after the October Revolution of 1917: origins, prospects and problems  at the same time, both heat and hydro and nuclear power plants were built, thereby increasing the installed capacity by more than 10 times in thirty years. After the collapse of the Soviet Union, there has been a halt in the pace of development of the Russian electric power industry, and now the deprecation of the fixed assets increase, the degradation of energy equipment, the aging of power generation technologies, the fall in investment attractiveness and the efficiency of management of generating capacities, which can lead to mass failure equipment and emergency consequences.The conclusion. Based on the results of the study, we have the following conclusions in the need to search for new mechanisms to improve the sustainability of the electricity industry in the absence of financial resources. In the author's opinion, it is advisable to implement them on three interrelated mechanisms: revising production capacities, eliminating potentially worn-out fixed assets; the formation of common programs for the development of the electric power industry within the framework of the General Electricity Market of the Eurasian Economic Union; the construction of power plants in the border areas, due to which several national states will provide electric power.